COVID-19, PREGNANT AND FEATURES OF THE STATE OF HYPERCOAGULABILITY (World Bulletin of Public Health, 2022)
COVID-19 is a global health emergency that can cause serious health problems during pregnancy. The aim of the study was: to assess the state of the hemostasis system in pregnant women with COVID-19. The research materials selected 49 pregnant women hospitalized in medical institutions of the Samarkand region due to COVID-19. In the results of the study, we mainly paid attention to the general condition of women depending on the trimester of pregnancy, the reasons for hospitalization, comorbid conditions, changes in general tests, coagulogram, in the blood coagulation system, as well as the outcomes of pregnancy and childbirth. Conclusion. As the burden and magnitude of COVID-19 continues to grow globally, there is still much to be learned about the impact of COVID-19 on pregnancy and perinatal and neonatal outcomes